Influence of Organizational Factors on Safety Performance in Oil and Gas Industry in the Niger Delta Region, Nigeria - , Ebubedike O. Okezie; , Ify L. Nwaogazie; , Patricks Chinemerem (Archives of Current Research International, 2023)
The aim of this study was to examine the influence of organizational factors on safety performance in oil and gas companies in the Niger Delta region of Nigeria. This is a cross-sectional study using questionnaires administered electronically to employees working in these companies to gather data on various organizational factors, including management commitment, communication, leadership, and worker involvement. The reliability of the instrument was assessed using Cronbach’s alpha, and path analysis was used to examine the relationships between organizational factors and safety performance. The results of the study showed that positive organizational factors tend to significantly influence safety compliance and participation positively, while they influence accidents and near misses negatively. These findings suggest that organizations should focus on improving organizational factors in order to enhance safety performance in the oil and gas industry.